Familial amyloidosis with cranial neuropathy and corneal lattice dystrophy. Issue 11 (November 1979) - Boysen, G; Galassi, G; Kamieniecka, Z; Schlaeger, J; Trojaborg, W
Abstract : Five siblings of a Danish family with slowly progressive involvement of the trigeminal, facial, glossopharyngeal, accessory, and hypoglossal nerves beginning at the age of 55-65 years were examined. All had asymptomatic corneal lattice dystrophy. Clinical and electrophysiological investigations also showed evidence of slight neurogenic involvement of the limbs. Conduction velocity along sensory nerves was normal but amplitude of sensory potentials was severely reduced suggesting an axonal affection which was confirmed by sural nerve biopsy. The neuropathy was secondary to amyloidosis revealed by skin and sural nerve biopsies.